Obzor mineralʹnykh resurov S.S.S.R. = Mineral resources of the U.S.S.R. - Soviet Union. (Mineral resources of the U.S.S.R., 1925)
Includes section "Literatura."
Some vols. have also distinctive titles.
Includes section "Literatura."
Title pages and table of contents in Russian and English; text in Russian.
Keywords: Mineral industries / Soviet Union.